URGENSI UNDANG-UNDANG PELINDUNGAN PEKERJA RUMAH TANGGA UNTUK KERJA LAYAK PEKERJA PERAWATAN - Izzati, Nabiyla Risfa (Faculty of Law, Universitas Diponegoro, 2024)
In Indonesia, care work is often not recognised as an economically valuable job. One type of care work commonly found in Indonesia is domestic work carried out by Domestic Workers. For more than 20 years, the Draft Law on the Protection of Domestic Workers has not been passed, showing that the recognition and protection of care workers are still far from expectations. This study aims to map the problem of decent work for care workers using a case study of domestic workers. Using socio-legal methods, this study concludes that there is an urgency to pass the Law on the Protection of Domestic Workers to guarantee decent work for domestic workers and as a symbolic momentum for the state's recognition of other care work.